Applied soils and micromorphology in archaeology - Macphail, Richard I. (Cambridge University, 2018)
"Applied Soils and Micromorphology in Archaeology provides the most up-to-date information on soil science and its applications in archaeology. Based on more than three decades of investigations and experiments, the volume demonstrates how description protocols and complimentary methods (SEM/EDS, microprobe, micro-FTIR, bulk soil chemistry, micro- and macrofossils) are used in interpretations. It also focuses on key topics, such as palaeosols, cultivation, and occupation surfaces, and introduces a range of current issues, such as site inundation, climate change, settlement morphology, herding, trackways, industrial processes, funerary features, and site transformation. Structured around important case studies, Applied Soils and Micromorphology in Archaeology is thoroughly-illustrated, with color plates and figures, tables and other ancillary materials on its website (www.cambridge.org/9781107011380); chapter appendices can be accessed separately using the web (www.geoarchaeology.info/asma). This new book will serve as an essential volume for all archaeological inquiry about soil."